Pengelolaan Reputasi Online Hotel melalui Platform Digital dalam Meningkatkan Brand Image: Best Practice Alila Villas Uluwatu Bali - Ni Made Gandhi Sanjiwani; Delfiana Da Costa (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
In 2024, the hotel room occupancy rate in Bali reached only 58.97%. This indicates that hotels must work diligently to manage their online reputation amid fierce competition. One of the best practices among hotels in Bali with a competitive online reputation and brand image is Alila Villas Uluwatu. This study aims to analyze how online reputation management through digital platforms can strengthen the brand image of Alila Villas Uluwatu. The study will explore the strategies and practices implemented by Alila Villas Uluwatu in building and maintaining their online reputation. Designed with a qualitative approach using in-depth interviews, social media analytics, observation, and document analysis, the findings of this research indicate that meticulous planning, structured organization, effective execution, and systematic control have a significant impact on enhancing the brand image of Alila Villas Uluwatu. The improvement in visibility and brand image is reflected in high engagement levels, reach, and impressions on social media, as well as positive ratings on review platforms. These results confirm that the POAC (Planning, Organizing, Actuating, and Controlling) strategy combined with content themed around Balinese culture and luxury successfully attracts audience attention and strengthens the brand image of Alila Villas Uluwatu. This research provides valuable insights for other hotels on how to manage online reputation to enhance brand image.